2019
DOI: 10.4149/bll_2019_005
|View full text |Cite
|
Sign up to set email alerts
|

Induction of miR-31 causes increased sensitivity to 5-FU and decreased migration and cell invasion in gastric adenocarcinoma

Abstract: Drug resistance is the main obstacle in the treatment of gastric cancer, the third most common cause of cancer-related death in the world. Due to their small size, easy entrance to cells and multiple targets, microRNAs (miRs) are considered novel and attractive targets. In the current study, parental MKN-45, MKN-45-control vector, and MKN-45-miR-31 populations were compared in terms of cell cycle transitions, migration, cell invasion, and proliferation. In addition, downstream targets of miR-31, including E2F6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 25 publications
(42 reference statements)
2
13
0
Order By: Relevance
“…23 Korourian et al indicated that the upregulation of miR-31 could increase the sensitivity of gastric cancer cells to 5-Fu in gastric adenocarcinoma. 24 Qin et al found that miR-106a could decrease the sensitivity of colorectal cancer cells to 5-Fu. 25 In the present study, we found that knockdown of miR-486-5p enhanced the inhibitory effects of 5-Fu on the migration and invasion of PANC-1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…23 Korourian et al indicated that the upregulation of miR-31 could increase the sensitivity of gastric cancer cells to 5-Fu in gastric adenocarcinoma. 24 Qin et al found that miR-106a could decrease the sensitivity of colorectal cancer cells to 5-Fu. 25 In the present study, we found that knockdown of miR-486-5p enhanced the inhibitory effects of 5-Fu on the migration and invasion of PANC-1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) belong to a class of small noncoding RNAs that are involved in development and diseases, making miRNAs an attractive tool and target for novel therapeutic approaches . Many miRNAs such as miR‐31 have been reported to be closely related to the development of GC, including the migration, metastasis, and the sensitivity to anticancer drugs of GC . miRNAs have also been reported to be associated with the initiation of chief cell transdifferentiation and apoptosis .…”
Section: Introductionmentioning
confidence: 99%
“…For example, overexpression of miR-939, miR-623, miR-429, miR-204, miR-124 or miR-31 was shown to enhance 5-FUinduced chemosensitivity by compromising tumor cell growth or inducing apoptosis. 9,[13][14][15][16][17][18][19] Among the above-mentioned miRNAs, miR-939 and miR-204 were the only two miRNAs with confirmed ability of reversing drug resistance both in vitro and in vivo, providing more convening evidence than others. 9,15 A role of miR-31 in chemosensitivity was reported by two separate research groups and may have more obvious effects.…”
Section: Microrna-based Chemotherapy Fluorouracil Resistancementioning
confidence: 99%
“…9,15 A role of miR-31 in chemosensitivity was reported by two separate research groups and may have more obvious effects. [17][18][19] Moreover, reduced miR-6785-5p, miR-193-3p, or miR-147 expression could also increase the chemosensitivity of GC to 5-FU. [20][21][22] Interestingly, miR-193-3p and miR-147 both target phosphatase and tensin homolog (PTEN) to exert their functions in GC.…”
Section: Microrna-based Chemotherapy Fluorouracil Resistancementioning
confidence: 99%